II mulino Del Po: entre a história e a ficção na escritura de Bacchelli - Tasca, Odete da Glória Oliveira (2016)
ABSTRACT: This article presents an analysis of the trilogy The Mill on the Po (1957), by Riccardo Bacchelli, a piece of work that portrays the complex story of a family of millers, which is seen in three successive generations. The novels include events of a whole century of history: from the period of Napoleon s defeat in Russia (1812) until the First World War (1918), and it depicts the banditry and the first social conflicts that occurred in the context of the struggle for Resurgence and Unification of Italy. In the perspective of the comparative studies and based upon reflections of writers such as Coutinho and Carvalhal (1994), Georg Lukacs (2011), Celia Fernández Prieto (2003), among others, a confrontation between the three novels that form the Bacchellian trilogy is established to compare the discourse of fiction with the discourse of History. This is done to acknowledge how the History of Italy dialogues with the fiction presented in the novel. It is also the objective of this research,through the use of some specific fragments of the novel, to analyze the poetic literary discourse in the rereading of the story, making sure the way the first one fictionalizes the official story and toshow how the popular masses begin to realize that they are the engine history. About the history of Italy s constitution, the novel also portrays the search for a national identity in this context. We notice, therefore, how Bacchelli s writing poeticizes the History through the use of a polysemic and metaphorical language, emphasizing also the question of religious discourse, making the reader notice, beyond the historical episode, a religious vision in the narrative, originated from popular traditions and legends. After some analysis of the characters relationship through life adversities, it is possible to comprehend that the human beings in Bacchelli s vision are temporal and historical beings. They are subjects of the flow of History and its irresistible force, but at the same time, through the matter that the History offers them, they have to build up their lives and confront their eternal destiny, for what they are also responsible. There is, consequently, a representation of human life in Bacchelli s writing between the material events of the human existence and the direction that is set beyond History